TEACHER'S USE OF AND STUDENTS' RESPONSES TO TEACHER'S GESTURE AND POSTURE IN THE TEACHING OF WRITING WITHIN THE GENRE BASED APPROACH. - Darin Fadhilah, - (2020)
Gesture is no longer an acts of moving the hand only but to assist people utterance. Simillary, the way people position their body means something and can affect the other people. In a classroom context, it is important for teachers to be aware of their gesture and posture in the process of teaching in the classroom. This study is a case study of how gestural and postural mode are used by the teacher in the teaching of writing within the genre-based approach. The students' responses toward the teacher's use of gestural and postural mode are analyzed. The study used observation, questionnaire, and interview to obtain the data. This study involves a senior high school teacher and a class of eleventh-grade students. The finding shows that the type of gesture used and its frequent follows the type of activity done within the genre-based approach stage. The gestural mode helps the teacher to explain, reduce teacher's talk, give instruction, and stimulate the discussion session within the classroom. The students responses' toward the teacher's use of gestural and postural mode show that the students agree whether the teacher's should be aware of their gesture and posture. The local-culture, the Sundanese culture, affects their opinion on the way teacher's point the students. The students agree that the teacher's gesture and posture can affect their mood in the process of learning and teaching.